A contribuição do Movimento Escoteiro na formação do profissional do ano 2020 - Souza, Sandra Joyce Silva de (2021)
Although little known, the Scout Movement moves more than 54 million Scouts in 171 countries; in Brazil, it reaches more than 111,000 members distributed throughout the national territory and is present in 745 cities. The Scout Movement or Scouting is a worldwide nonformal education movement, voluntary, non-partisan, and non-profit, founded in 1907 by military man Robert Stephenson Smith Baden-Powell. The purpose of the Scout Movement is to commit the development of young people through a system of values that prioritize learning by doing. This system is based on the Scout Promise and Law, teamwork, and outdoor living. This study aimed to understand whether the Scouting environment contributes to its young members to develop professional potentials in line with those required in the year 2020, described through a publication by the World Economic Forum. In order to base the theoretical foundation of this research, it was necessary to qualify the concepts through bibliographical and bibliometric research, exploring the theoretical indications of the Scout Movement, Knowledge, Skills, and Professional Competencies of the Year 2020. The field research on which this study is based was carried out with the application of a questionnaire. The data analysis was performed using the Quantitative Content Analysis Method. In the end, some notes are made about the scenario studied